Digitalization on business model innovation: a systematic literature review on current studies - Suswanto, Budyi; Priyo Purnomo, Eko; Hadiyati , Ernani (Bulletin of Social Informatics Theory and Application, 2024)
This research examines business model innovation (BMI), which has recently received attention from academics and practitioners due to the enhancement of global competition and the constant need to adapt to the changing environment. Therefore, the main objective of this study is to provide an overview of state-of-the-art research on business model innovation by conducting a systematic literature review. The author's review provides a deeper understanding and detail on the main components of Business Model Innovation (BMI). Likewise, the author's research identifies the role of digitalization in Business Model Innovation. This study comprises a comprehensive literature evaluation with a particular focus on studies linked to the use of digital technologies and business models to understand better attempts to promote the usage of digital systems. This study aims to promote the academic conversation about how industrial companies might use digital technologies to innovate business models and create a sustainable industry. Implementing new business models that promote the implementation of digital systems necessitates an essential shift of the corporate ecosystem into one in which appreciation is jointly generated by suppliers, environment partners, and consumers through resource optimization and efficient functioning and use of technology.